Finite Element Analysis and Structure Improvement of 16t Steering Drive Axle Housing Assembly - Hu Shun’an; Xu Yuanzhou; Song Jianping; Wang Lishuai (Jixie chuandong)
In the process of road test of the large tonnage drive axle,an abnormal wear failure occurred between the yoke of steering driving axle and the universal drive shaft assembly. The lacking stiffness of axle housing assembly causes the failure after finite element analysis（ FEA）. So the axle housing assembly needs to be improved. The stiffness of improved axle housing assembly meets the design requirements based on FEA.But when loading to maximum,the safety coefficient of axle housing assembly is small. After comparing the FEA results with the test bench results of improved axle housing assembly,the FEA results are near to the test bench results by removing the influence of human and system deviation.